The mutual friend : [large type] a novel - Bays, Carter, 1975- (Thorndike Press large print core, 2022)
"It's the summer of 2015, and Alice Quick needs to get to work. She's twenty-eight years old, grieving her mother, barely scraping by as a nanny, and freshly kicked out of her apartment. If she can just get her act together and sign up for the MCAT, she can start chasing her dream of becoming a doctor . . . but in the Age of Distraction, the distractions are so distracting. There's her tech millionaire brother's religious awakening. His picture-perfect wife's emotional breakdown. Her chaotic new roommate's thirst for adventure. And, of course, there's the biggest distraction of all: Love. From within the story of one summer in one woman's life, an epic tale is unearthed, spanning continents and featuring a tapestry of characters tied to one another by threads both seen and unseen. Filled with all the warmth, humor, and heart that gained How I Met Your Mother its cult following, The Mutual Friend captures in sparkling detail the chaos of contemporary life, a life lived simultaneously in two different worlds--the physical one and the one behind our screens--and reveals how connected we all truly are"--